ANALISIS FUNGSI PRODUKSI USAHA TERNAK SAPI DI KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - Thamrin, Aprilia M; Elly, Femi H; Santa, Nansi M; Manese, Merry A.V (Universitas Sam Ratulangi, 2019)
PRODUCTION FUNCTION ANALYSIS OF CATTLE FARMING IN WEST TOMPASO DISTRICT REGENCY OF MINAHASA.Farmers in West Tompaso districtÂ cultivatedBeef cattle traditionally and not as main farming.The government in this case also encourages farmers to increase production. The problem is whether the production factor used affects the production of beef cattle.Â The research aims to determine the factors affecting cattle production. The data collected is primary data and secondary data. Sampling uses the Cluster Random Sampling method. The analysis of the data used is multiple regression with econometrics approaches and software using SAS program 9.4. The results showed that the respondents ' lifespan ranged from 30-65 years to categorized productive age. Based on the results of the study can be concluded that together the factors of land production, labor and feed are real effect on the production of beef cattle. Land production and feed factors that have real effect on the production of beef cattle.Keywords: Land, labor, feed, beef cattle